2016
DOI: 10.1590/1413-81232015215.07822015
|View full text |Cite
|
Sign up to set email alerts
|

Impacto das equipes de saúde bucal da Estratégia da Saúde da Família na saúde bucal de adolescentes do sul do Brasil

Abstract: (RM = 0,64 IC95%; 0,94 (RM = 0.64 CI 95%, 0.43 to 0.94).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
29

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 10 publications
0
15
0
29
Order By: Relevance
“…al. 24 suggested that the improvement in access with the presence of oral health in the Family Health Strategy did not culminate with the improvement in the oral health of the users in the studied regions.…”
Section: Discussionmentioning
confidence: 91%
“…al. 24 suggested that the improvement in access with the presence of oral health in the Family Health Strategy did not culminate with the improvement in the oral health of the users in the studied regions.…”
Section: Discussionmentioning
confidence: 91%
“…Neste estudo, maior prevalência do desfecho também ocorreu quando a proporção de internações sensíveis à atenção básica foi menor que 28% e quando a proporção de exodontias entre procedimentos selecionados foi menor que 8%. As evidências científicas convergem ao apresentar os efeitos da implantação da Estratégia Saúde da Família na saúde da população, associando-a à redução da mortalidade infantil, ao declínio de hospitalizações evitáveis, ao aumento da oferta de trabalho entre os adultos e ao aumento da matrícula escolar 31 .…”
Section: Discussionunclassified
“…A cross-sectional school-based study was conducted. The database used was obtained from previous research 11 , which included an analysis of the oral health profile of 1771 school-going adolescents aged 15 to 19 years, from 36 municipalities with fewer than 50 thousand inhabitants in southern Brazil, carried out between June and December 2011. The required sample of 1771 adolescents was found by estimating a level of significance of 0.05 and a power of 95%, a non-response rate of 20% and a design effect of 1.5.…”
Section: Methodsmentioning
confidence: 99%